2013
DOI: 10.4049/jimmunol.1203575
|View full text |Cite
|
Sign up to set email alerts
|

Prenatally Acquired Vitamin A Deficiency Alters Innate Immune Responses to Human Rotavirus in a Gnotobiotic Pig Model

Abstract: We examined how prenatally acquired vitamin A deficiency (VAD) modulates innate immune responses and human rotavirus (HRV) vaccine efficacy in a gnotobiotic (Gn) piglet model of HRV diarrhea. The VAD and vitamin A sufficient (VAS) Gn pigs were vaccinated with attenuated HRV (AttHRV) with or without concurrent oral vitamin A supplementation (100,000IU) and challenged with virulent HRV (VirHRV). Regardless of vaccination status, the numbers of conventional and plasmacytoid dendritic cells (cDCs and pDCs) were hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(86 citation statements)
references
References 82 publications
8
78
0
Order By: Relevance
“…Booster vaccinations in later life do not seem to result in restoration of the impairment observed in early life 38,39 . This is in line with a study in pigs in which induced vitamin A deficiency in sows impaired vaccination in the offspring that could not be rescued by dietary supplementation 50 . Furthermore, nasal washes of infants from malnourished mothers have low levels of immunoglobulin A, an antibody isotype produced at mucosal sites in structures such as the Peyer's patches 51 .…”
Section: Lymphoid Organogenesissupporting
confidence: 87%
“…Booster vaccinations in later life do not seem to result in restoration of the impairment observed in early life 38,39 . This is in line with a study in pigs in which induced vitamin A deficiency in sows impaired vaccination in the offspring that could not be rescued by dietary supplementation 50 . Furthermore, nasal washes of infants from malnourished mothers have low levels of immunoglobulin A, an antibody isotype produced at mucosal sites in structures such as the Peyer's patches 51 .…”
Section: Lymphoid Organogenesissupporting
confidence: 87%
“…As described previously, 10 5 cells were stained with mouse anti-porcine CD3e-FITC (SouthernBiotec, Birmingham, Alabama, USA), mouse anti-porcine CD21-FITC (SouthernBiotec, Birmingham, Alabama, USA), mouse anti-porcine SWC1-FITC (AbD Serotec, Raleigh, NC, USA) and mouse anti-porcine SWC9-FITC (AbD Serotec, Raleigh, NC, USA) monoclonal antibodies (mAb) to characterize the frequencies of T cell, B cell, granulocyte/monocyte and macrophage and to determine the purity of isolated DCs by flow cytometry (Vlasova et al, 2013). Acquisition of 50,000 events was conducted using MACSQuant ® Analyzer flow cytometer (Miltenyi Biotec, San Diego, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…These studies have shown a general role of vit A in regulating gut mucosal immune responses. To determine the effect of VAD and supplementation on oral RV vaccines, prepartum VAD was established by manipulating sow dietary vit A levels, and the derived Gn piglets were used as a VAD model (118). The VAD piglets were characterized by significantly lower hepatic vit A levels compared with vit A-sufficient (VAS) pigs from vit A-supplemented sows (118).…”
Section: Vitamin a As Adjuvant For Oral Rv Vaccines In Neonatal Pigsmentioning
confidence: 99%
“…To determine the effect of VAD and supplementation on oral RV vaccines, prepartum VAD was established by manipulating sow dietary vit A levels, and the derived Gn piglets were used as a VAD model (118). The VAD piglets were characterized by significantly lower hepatic vit A levels compared with vit A-sufficient (VAS) pigs from vit A-supplemented sows (118). Vaccinated (33 attenuated RV) VAD pigs had higher diarrhea severity scores compared with vaccinated VAS pigs, which coincided with lower serum IgA RV antibody titers and significantly lower intestinal IgA ASC post challenge in the former groups, suggesting lower anamnestic IgA antibody responses owing to VAD (119).…”
Section: Vitamin a As Adjuvant For Oral Rv Vaccines In Neonatal Pigsmentioning
confidence: 99%